2009
DOI: 10.1037/a0015732
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of social factors and nonsuicidal self-injury among young adults.

Abstract: Retrospective reports of social influences in nonsuicidal self-injury (NSSI) with regard to initiation, disclosure, methods, and motivations for engaging in the behaviour were examined in 23 (2 male, 21 female) self-injuring university students. Parent and peer social support was compared between the NSSI group and a comparison group that did not engage in NSSI. Lifetime frequency of NSSI and social support were evaluated. NSSI behaviours were found to be highly socially influenced in several ways, with 65% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 37 publications
8
77
0
1
Order By: Relevance
“…To our knowledge, only a few other studies have examined the relationship between social capital and DSH. Several found that social support was inversely associated with prevalence of DSH (Heath et al, 2009;Kong et al, 2014). For example, nursing students with social support were less likely to deliberately self harm (Kong et al, 2014).…”
Section: Social Capital Uncertainty Stress and Dshmentioning
confidence: 96%
See 1 more Smart Citation
“…To our knowledge, only a few other studies have examined the relationship between social capital and DSH. Several found that social support was inversely associated with prevalence of DSH (Heath et al, 2009;Kong et al, 2014). For example, nursing students with social support were less likely to deliberately self harm (Kong et al, 2014).…”
Section: Social Capital Uncertainty Stress and Dshmentioning
confidence: 96%
“…Foreign studies also found that trust and reciprocity are the strongest predictors of self-rated health and psychological wellbeing (Heath et al, 2009). Cognitive social capital might influence DSH behavior through increasing individual sense of trust and belonging.…”
Section: Social Capital Uncertainty Stress and Dshmentioning
confidence: 98%
“…Compared to individuals without a history of NSSI, those with NSSI report pervasive interpersonal problems, including poorer quality relationships with peers and caregivers (Claes, Houben, Vandereycken, Bijttebier, & Muehlenkamp, 2010;Gratz, Conrad, & Roemer, 2002;Hilt, Nock, Lloyd-Richardson, & Prinstein, 2008;Hoff & Muehlenkamp, 2009), greater loneliness (Giletta, Scholte, Engels, Ciairano, & Prinstein, 2012;Glenn & Klonsky, 2013;Guertin, Lloyd-Richardson, Spirito, Donaldson, & Boergers, 2001), higher rates of peer victimization (Giletta et al, 2012;Hilt et al, 2008), lower perceived support (Heath, Ross, Toste, Charlebois, & Nedecheva, 2009;Muehlenkamp, Brausch, Quigley, & Whitlock, 2013), and worse social problem-solving abilities (Nock & Mendes, 2008). Recent interpersonal theories of NSSI propose that interpersonal experiences may contribute to the development and maintenance of NSSI as both antecedents (e.g., rejection, conflict) and consequences (e.g., support) of this behavior (Nock, 2008(Nock, , 2009Prinstein, Guerry, Browne, & Rancourt, 2009;Yates, 2004).…”
Section: Cihr Author Manuscriptmentioning
confidence: 99%
“…Nearly half of adolescents who self-injure report social sources for how they learned about NSSI, including observing or learning from peers (38%) and media (13%), while 17% to 20% report that NSSI behavior is not socially learned (e.g., "I just wanted to try"). Surprisingly, 28% to 39% were unable to pinpoint where or how they learned about NSSI (Deliberto & Nock, 2008;Heath, Ross, Toste, Charlebois, & Nadecheva, 2009), which highlights the need for in-depth research regarding the means through which NSSI knowledge is acquired, as well as an exploration of potential differences between adolescents who recall the origin of NSSI behaviors and those who do not. Future research in this area should also explore source overlap (e.g., those who selfdiscovered but were also socially influenced to try NSSI regularly or use specific methods).…”
Section: Initiation Of Nssimentioning
confidence: 99%
“…NSSI has typically been studied in adolescents because the reported average age of onset is 12 to 14 years (Deliberto & Nock, 2008;Heath, Ross, Toste, Charlebois, & Nadecheva, 2009). …”
Section: Purpose and Hypothesesmentioning
confidence: 99%